Plan de marketing para el restaurant Romasag de la ciudad de Loja - Sanmartín Granillo, Rosa Magdalena (2016)
Today is vital that companies have a Marketing Plan as a key tool for achieving the goals of any business or organization. That is why this thesis general objective "MARKETING PLAN FOR ROMASAG RESTAURANT OF THE CITY OF LOJA” in order to contribute to the organizational development of the company in study Methodological procedures or guidelines, allow the researcher to walk on the aspects required to integrate the different phases of research, the methods are the ways that the researcher knows certainly where they have to go in its research process , techniques tools which methods are supplied for both primary data collection phase and secondary tools without which methods would not have consistency when applying the methodological analysis historical , deductive , inductive, analytical , statistical and systematic approach : To meet the objectives the following methods and techniques were used , as follows . Within the technical literature collection to gather the necessary information on strategic planning , direct observation through field visits to the company " ROMASAG " more than this 200 surveys applied to clients and 6 employees applied the company " ROMASAG " and interview the manager of the same Mr. Juan Carlos Sanmartín Granillo . Then the results of the information obtained, where the situational analysis of the company to analyze the external aspects of the environment was held, also the internal aspects, in order to establish the current status of how the company is presented. Thus we have the EFE matrix with a value of 2.76 points which means that there is a predominance of opportunities Threat; while EFI matrix with a value of 2.96 points, which means that there is a predominance of strengths over weak nesses. Later to formulate the strengths weak nesses, opportunities and threats for the design of the SWOT matrix, allowing it to determine the strategic objectives with their respective budgets and responsible; so we have: "Train personnel RESTAURANT ROMASAG to achieve greater efficiency and leverage the trust and good availability of employees" "Make a plan advertising and promotion for the ROMASAG RESTAURANT in order to attract more customers and achieve greater market position." “Ask a better presentation and decoration of menus served with an attractive presentation to customers at the time of serving." Train employees of the company "ROMASG" in order to improve customer service, It is noted that the implementation of the four strategic objectives at a cost of $6390. Finally, conclusions and recommendations, which arises, the manager of the company "ROMASG" the importance of the implementation of the Marketing Plan, as this will allow you to position themselves in the minds of consumers and then reach their fidelity is presented . So that sales and company profits will increase. Raw materials (vegetables, meats, seafood, sweet spices and saldas) that will give a boost in aroma, flavor, color is used exquisite, featuring striking features quality customer Besides recommending that a perfect monitor compliance with the objectives is made, and periodically analyze its effectiveness in increasing the share market share of the company. To generate a competitive advantage through better presentation of menus that are appealing and attractive to customers